Komunikasi Rekonsiliasi Bingkai Ale Rasa Beta Rasa Provokator Damai Salam Sarane di Kota Ambon Maluku - Noviawan Rasyid Ohorella; Budi Santoso (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2021)
This study aims to determine and analyze the reconciliation process carried out after the 1999 conflict in Ambon City, Maluku Province. The method used is a descriptive qualitative approach, in which the researcher makes observations involved, in-depth interviews, FGDs, and documentation of the object under study. The theory used is the Symbolic Interactionist and Decision Making, Identification, and Control. The results showed that the reconciliation carried out by peaceful provocateurs used symbols in the frame of brotherhood such as Salam Sarane and Place of Worship. After the 99 conflict in Maluku, Ambon City became the window of world civilization agreed in the world peace gong. The reconciliation effort in realizing peace is a strategic step taken by combining socio-cultural and religious values. Efforts made in the form of Dialogue and Meetings both within the community and places of worship. Suggestion that the researcher can give is that the Peace Provocateurs must put themselves in place and improve their capability in facing the social behavior of the Maluku people going forward.